STUDI SUHU DAN KELEMBABAN RUMAH PENDERITA ISPA PADA BALITA DI DESA GANDATAPA KECAMATAN SUMBANG KABUPATEN BANYUMAS TAHUN 2018 - Nilam Safitri Ariani; M. Choiroel Anwar (Poltekkes Kemenkes Semarang, 2019)
One of factors risk the occurrence of URIs disease are temperature and humidity that do not eligible for health requirements. Gandatapa village is a region with a high rate of URIs disease reached 49 patients. The purpose of this study to determine the quality of temperature and humidity in the home of patients with ARI in Gandatapa village, Sumbang sub district, Banyumas regency. The method used in this research is descriptive method by taking 49 houses or the total of patients with URIs by measuring in the sleeping room and family room. The result of the research showed that the patient of URIs in Gandatapa Village was known that the temperature in the sleeping room was eligible (73,47%) and the temperature in the eligible family room (83,67%), humidity in the eligible sleeping room (65,31%) and humidity in eligible family room (61,22%). The conclusion from the results, home temperature URIs patient in the eligible sleeping room thirty six houses and the temperature in the eligible family room fourty one houses, humidity in the eligible sleeping room seventeen houses and humidity in eligible family room nineteen house